2021
DOI: 10.1155/2021/5525118
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Multiple Organ Failure Complicated by Moderately Severe or Severe Acute Pancreatitis Based on Machine Learning: A Multicenter Cohort Study

Abstract: Background. Multiple organ failure (MOF) may lead to an increased mortality rate of moderately severe (MSAP) or severe acute pancreatitis (SAP). This study is aimed to use machine learning to predict the risk of MOF in the course of disease. Methods. Clinical and laboratory features with significant differences between patients with and without MOF were screened out by univariate analysis. Prediction models were developed for selected features through six machine learning methods. The models were internally va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…In the test dataset, the onset of AP and SAP were also more commonly seen in male than in female patients and the median age ranged from 44 to 47 years. Consistent with what Xu et al (2021) reported, biliary sludge or gallstones (39.49%) was the most frequent etiology of AP in our cohorts, followed by hypertriglyceridemia (17.87%). No statistical differences were observed in sex, age, smoke, history of hypertension, and diabetes in two groups of three datasets (p > 0.05).…”
Section: Demographic and Clinical Characteristicssupporting
confidence: 92%
See 1 more Smart Citation
“…In the test dataset, the onset of AP and SAP were also more commonly seen in male than in female patients and the median age ranged from 44 to 47 years. Consistent with what Xu et al (2021) reported, biliary sludge or gallstones (39.49%) was the most frequent etiology of AP in our cohorts, followed by hypertriglyceridemia (17.87%). No statistical differences were observed in sex, age, smoke, history of hypertension, and diabetes in two groups of three datasets (p > 0.05).…”
Section: Demographic and Clinical Characteristicssupporting
confidence: 92%
“…Machine learning (ML) applied in medicine, both supervised and unsupervised, is becoming increasingly popular based on its efficient computing algorithms to learn from massive clinical data (Deo, 2015). Previous studies (Han et al, 2022;Liu et al, 2022;Xu et al, 2021;Yang et al, 2021;Zhang et al, 2021;Zhao et al, 2021;Zhou et al, 2021) have confirmed that ML has great potential in building models for disease diagnosis, prognosis prediction, survival analysis, etc. Traditional ML includes logistic regression (LR), support vector machine (SVM), random forest, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Choi et al combined clinical (i.e., APACHE-II and BISAP scores) and radiologic (i.e., Balthazar grade and EPIC score) scoring systems by classification tree analysis for predicting SAP (Choi et al, 2018). Xu et al reported that adaptive boosting algorithm (AdaBoost) could predict development of multiple organ failure, complicated by moderately severe or severe AP (Xu et al, 2021). However, the above models were limited due to lack of individualized prediction on the test sample.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies which have evaluated the utility of AI in acute pancreatitis for predicting severity, organ failure, mortality, venous thromboembolism, etc 4 . Table 1 shows data from eight studies of which five have evaluated the role of AI in predicting severe acute pancreatitis and three for predicting organ failure (which also denotes a severe disease) 5–12 . These studies differ in the methodologies and algorithms used and some have applied more than one AI technique to arrive at the best model.…”
Section: Study Reference Ai Technique Predictors* Sample Size (N) Out...mentioning
confidence: 99%